2010
DOI: 10.1177/0961203310366855
|View full text |Cite
|
Sign up to set email alerts
|

Good outcomes with mycophenolate-cyclosporine-based induction protocol in children with severe proliferative lupus nephritis

Abstract: The outcomes of children with severe proliferative lupus nephritis (LN) were examined using a new mycophenolate and cyclosporine-based (MMF-CSA) induction protocol. Sixteen children with LN (WHO class III and IV), 31.3% of whom required dialysis at induction, were retrospectively studied. Median MMF dose was 942 mg/m( 2)/day. Thirteen patients (81%) with persistent proteinuria received CSA. Clinical and laboratory parameters were compared at pre-induction, 6 and 12 months. Treatment outcome was defined by Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…When combining the high-quality evidence from RCT for LN in adult-onset SLE with the evidence from smaller case series and observational cohort studies in cSLE, the expert group recommends MMF (1200-1800mg/m2/day, maximum 1500 mg twice daily) or I.V. CYC in combination with high-dose prednisone (1-2 mg/kg/day, maximum 60 mg/day) for induction treatment of proliferative LN in cSLE (10,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). The dosing of I.V.…”
Section: Induction Treatmentmentioning
confidence: 99%
“…When combining the high-quality evidence from RCT for LN in adult-onset SLE with the evidence from smaller case series and observational cohort studies in cSLE, the expert group recommends MMF (1200-1800mg/m2/day, maximum 1500 mg twice daily) or I.V. CYC in combination with high-dose prednisone (1-2 mg/kg/day, maximum 60 mg/day) for induction treatment of proliferative LN in cSLE (10,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). The dosing of I.V.…”
Section: Induction Treatmentmentioning
confidence: 99%
“…206,207 Proteinuria in children is defined by a spot urine protein/creatinine (Up/c) of greater than 0.2 mg/mg creatinine or by a 24-hour urine collection containing protein greater than 4 mg/m 2 /hour. [240][241][242][243][244][245][246][247][248][249] However, there have been no large-scale randomized, controlled trials in pediatric LN; treatment primarily has been determined from the adult studies collection is necessary to eliminate false readings due to the possible contribution of orthostatic proteinuria. Given the cumbersome nature of 24-hour urine collection, and the possible unreliability in young or incontinent children, Up/c determination is a convenient and reliable method for evaluating and following LN in children and shows good correlation with 24-hour urine collection.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Cyclosporin A Cyclosporin A (Cyc A) can also be used in LN, but there are only a few trials involving a small number of patients studying the effects of it on LN [4]. Aragon et al [31] showed that together with MMF, Cyc A has been an alternative agent in the induction therapy in children with severe LN. There are also studies in children showing its effectiveness as a treatment option in the treatment of refractory cases of LN, but with high relapsing rates after cessation of the therapy [32,33].…”
Section: B-lymphocyte Depletion Therapymentioning
confidence: 99%